2016
DOI: 10.1098/rspb.2016.0821
|View full text |Cite
|
Sign up to set email alerts
|

A neo-W chromosome in a tropical butterfly links colour pattern, male-killing, and speciation

Abstract: Sexually antagonistic selection can drive both the evolution of sex chromosomes and speciation itself. The tropical butterfly the African Queen, Danaus chrysippus, shows two such sexually antagonistic phenotypes, the first being sex-linked colour pattern, the second, susceptibility to a male-killing, maternally inherited mollicute, Spiroplasma ixodeti, which causes approximately 100% mortality in male eggs and first instar larvae. Importantly, this mortality is not affected by the infection status of the male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 42 publications
3
61
0
Order By: Relevance
“…Here, we confirm that the chromosome number for D. chrysippus is also n = 30 [de Lesse and Condamin, 1962;Gupta, 1964;Smith et al, 2016] for males from Southeast Asia, Israel, Ghana, Watamu (Kenya), and Kitengela (Kenya) (examples shown in Fig. 7 a, b).…”
Section: Danaus Chrysippussupporting
confidence: 65%
See 1 more Smart Citation
“…Here, we confirm that the chromosome number for D. chrysippus is also n = 30 [de Lesse and Condamin, 1962;Gupta, 1964;Smith et al, 2016] for males from Southeast Asia, Israel, Ghana, Watamu (Kenya), and Kitengela (Kenya) (examples shown in Fig. 7 a, b).…”
Section: Danaus Chrysippussupporting
confidence: 65%
“…The population is part of a large hybrid zone between the subspecies D. c. dorippus and D. c. chrysippus . Females from this population display a sex chromosome trivalent, neoW/Z 1 Z 2 , besides 28 bivalents in meiosis and are infected with a male-killing bacterium, Spiroplasma ixodetis [Smith et al, 2016]. The neoW is interpreted as the result of a fusion between the original W chromosome and an autosome, carrying the phenotypically defined wing colour gene C [Smith et al, 2010].…”
Section: Danaus Chrysippusmentioning
confidence: 99%
“…1A). However, crosses with females from the contact zone revealed that the BC chromosome has become sex linked, forming a neo-W that is unique to this population [19,22]. Since female meiosis is achiasmatic (it lacks crossing-over) in the Lepidoptera, the formation of a neo-W would instantaneously cause perfect linkage, not just of the B and C loci, but of an entire nonrecombining chromosome, along with other maternally-inherited DNA.…”
Section: Introductionmentioning
confidence: 96%
“…What is particularly striking is that the presence of the neo-W coincides with infection by a maternally-inherited 'male killer' endosymbiont related to Spiroplasma ixodetis, which kills male offspring and leads to highly female-biased sex-ratios where infection is common [22][23][24]. The combination of neo-W and male killing is expected to dramatically alter the inheritance and evolution of the BC chromosome [22,25]: Infected females typically give rise to all-female broods who should always inherit the same colour patterning allele on their neo-W, along with the male-killer, while the other maternal allele is systematically eliminated in the dead sons ( Fig. 1B), forming a genetic sink for all colour pattern alleles not on the neo-W.…”
Section: Introductionmentioning
confidence: 99%
“…For both of these reasons, sex chromosome turnover may be a particularly important driver of population divergence and speciation. Indeed, associations between neo-sex chromosomes and speciation are reported in stickleback (Kitano et al 2009), swordtail (Franchini et al 2018), Hessian fly (Benatti et al 2010), mountain pine beetle (Bracewell et al 2017), and the African Queen butterfly (Smith et al 2016).…”
mentioning
confidence: 99%